Knowledge, Prevention, and Practice of Heat Strokes Among the Public in United Arab Emirates (UAE) - Alebaji, Mohamad Baraa; Elzini, Tasnim Hossam; Shahin, Haneen Basim Ali; Suleiman​​, Abdelwahab Bashir Mohamed; Richard, Harshitha; Dali, Raed Imad Aldin (International Journal of Medical Students, 2022)
Background: Heat stroke is a predictable and preventable occurrence. Public awareness of the condition and preventative practices are essential in hot and humid regions. This study aims to assess the level of awareness (knowledge, prevention, and management) of heat stroke among United Arab Emirates (UAE) residents. Methods: This is a survey-based study of knowledge and practices of heat stroke in a random sample of adults (?18 years) in four different cities in the UAE. Each correct answer was equal to one point, and total and average scores were calculated, with the average score used as the cutoff point. Multivariate logistic regression was used to identify factors associated with below-average awareness. Results: A total of 402 people participated in the study, with an average age of 33±12 years, and 48.5% were female. Only 1 person achieved a perfect score, and 0.7%, 10%, and 17.7% achieved above-average scores in knowledge, practices, and management, respectively. Seven percent of participants had never heard of a heat stroke. A third of participants (32%) were unaware that severe heat strokes could lead to death. Males are at a higher risk of having a poor level of knowledge (Odds ratio [OR]=1.65; 95% confidence interval [95%CI]=1.10-2.47). The older the population, the poorer the knowledge of heat stroke was (OR=1.39, 95%CI=1.03–1.89). Conclusion: The results of this study show that a huge proportion of the population in the UAE does not have sufficient knowledge about heat stroke, its prevention, and management. Governmental institutes should increase awareness of heat stroke.